Selection of Bacillus thuringiensis Strains Toxic Against Cotton Aphid, Aphis gossypii Glover (Hemiptera: Aphididae) - Monnerat, Rose Gomes; Melatti, Viviane; Praça, Lílian; Martins, Érica; Sujii, Edison; Berry, Colin (BioAssay, 2010)
The applied biological control of the cotton aphid, Aphis gossypii, using Bacillus thuringiensis is a viable alternative. It was, recently, demonstrated that this bacterium can circulate inside the plant in a systemic way allowing its utilization in the control of sucker insects. This work aimed to establish a methodology for selective bioassay of B. thuringiensis against A. gossypii and select toxic strains for the control of this insect. An initial bioassay was conducted using a B. thuringiensis strain marked with the gene gfp (“green fluorescence protein”), that allowed the visualization by fluorescence microscopy of the bacteria in a macerate of the insects after feeding on plants treated with the bacteria, thus confirming the exposure of the insect to this control agent. Four hundred strains of B. thuringiensis belonging to the Collection of Bacillus spp. from Embrapa Genetic Resources and Biotechnology were tested through this bioassay method and five of them (S29, S40, S616, S1168, and S1576) caused mortality above 50%. From these, S29 strain showed the highest toxicity. The results found in this work demonstrate the efficiency of the methodology, since the toxicity of B. thuringiensis was confirmed against the cotton aphid, when applied to cut stems of cotton plants.